2017
DOI: 10.11646/zootaxa.4362.1.1
|View full text |Cite
|
Sign up to set email alerts
|

The vespid fauna of Pakistan

Abstract: This study provides the first annotated check list of the Vespidae of Pakistan. It is based on the National Insect Museum collection and various studies in Pakistan. Among 105 identified taxa, 77 species and 28 subspecies are recorded in the four subfamilies Eumeninae, Masarinae, Polistinae and Vespinae. Three new records for the fauna of Pakistan are added, namely Anterhynchium mellyi, Antepipona ovalis and Eumenes coronatus coronatus. Among the total, 12 species/subspecies are endemic to Pakistan, namely Anc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 773 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Further research is needed to understand how this difference is real or it results from lack of samples. Although many papers cite the species occurring in China [Das, Gupta, 1989;Carpenter, 1996;Rafi et al, 2017] no exact localities are reported in literature. Also Tan et al [2014] in their work about the subgenus Gyrostoma Kirby, 1828 in China wrote "No specimens from China were available" and mentioned P. watti among Chinese wasp fauna because recorded from China by Gupta [1984, 1989] and Carpenter [1996].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further research is needed to understand how this difference is real or it results from lack of samples. Although many papers cite the species occurring in China [Das, Gupta, 1989;Carpenter, 1996;Rafi et al, 2017] no exact localities are reported in literature. Also Tan et al [2014] in their work about the subgenus Gyrostoma Kirby, 1828 in China wrote "No specimens from China were available" and mentioned P. watti among Chinese wasp fauna because recorded from China by Gupta [1984, 1989] and Carpenter [1996].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the data come from Pakistan and India. In the first country, P. wattii is recorded in all provinces exept Balochistan [Das, Gupta, 1984, 1989Gusenleitner, 2007;Mahmood et al, 2012;Siddiqui et al, 2015;Faiz et al, 2016;Habib et al, 2017;Rafi et al, 2017;A.K. Khan et al, 2017;K.…”
Section: Introductionmentioning
confidence: 99%
“…This study was the first attempt to find out the diversity of Vespidae in the area. Various faunistic works on the Vespidae of Pakistan are available 21 but the present study explores the diversity among species of Vespidae with application of various diversity indices. A total of 24 species were identified from a sample size of 2397 individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Genus vespula thomson, 1869: Vespula flaviceps (Smith, 1870): Material examined: Ghizer: Gahkuch, 1♀, 25-iii-11, leg. Hina; Remarks: Earlier reported this species from Khyber-Pakhtunkhwa: Nathia Gali, Swat, Batgram; Punjab: Murree (Dvořák, 2007;Mahmood et al, 2012;Rafi et al, 2017); Distribution: China; Nepal; Pakistan; Korea; Laos; India; Japan; Myanmar; Taiwan; Russia; Thailand (Carpenter and Kojima, 1997;Dvořák, 2007;Mahmood et al, 2012).…”
Section: Family Vespidaementioning
confidence: 98%
“…Hina; Remarks: Osmia cornifrons has been reported by Hussain et al (2010) from Skardu; Distribution: Europe, Southwestern Asia, North America (Michener, 2007). (Dvořák, 2007;Mahmood et al, 2012;Siddiqui et al, 2015;Faiz et al, 2016Rafi et al, 2017;Rauf et al, 2018); Distribution: China; Bhutan; Afghanistan; India; Malaysia; Indonesia; Laos; Myanmar; Nepal; Pakistan; Vietnam; Taiwan; Thailand; introduced into Belgium; Tsushima; Korea; France; Italy; Portugal; Spain; Yemen (Carpenter and Kojima, 1997;Dvořák, 2007;Mahmood et al, 2012).…”
Section: Family Halictidaementioning
confidence: 99%